The use of an ethological approach to evaluate consumers' appreciation of luxury facial skincare and discriminate between products: A preliminary study. (June 2016) - Bourguet, Cécile; Pêcher, Christelle; Bardel, Marie-Héloïse; Navarro, Séverine; Mougin, Danielle
Highlights: A detailed ethogram specific to the context of use of skincare was developed. Behavioral analysis showed that one product was appreciated more than the other. The behavioral analysis provided information on product-induced consumer feelings. The behavioral analysis translated how the texture of the products was perceived. Abstract: The hedonic dimension of products is a central challenge for cosmetic companies. It is widely measured by liking ratings of the products by consumers, but although this method does help to understand consumer choices, it also carries several experimental biases and provides no information on consumers' feelings. Here we tested the relevance of combining consumers' liking ratings with a detailed behavioral approach involving analysis of activities, postures, gazes, and head and body movements of consumers during skincare application to discriminate two products. The sensory characteristics of the two products were also described by a panel of experts. Results showed that behavioral analysis was able to discriminate the two products in terms of satisfaction whereas liking ratings assessment failed to distinguish them. Behavioral analysis also provided relevant complementary information on consumers' feelings during and after product application, such as interest, detachment or physical comfort. When linked to the sensorial evaluation, the study of behavioral reactions helped understand how the two products' respective sensory characteristics were perceived by consumers. This preliminary study brings new insight with promising perspectives for research on cosmetics and consumer products in general.